FORMULATION AND EVALUATION OF LIP JELLY BY REPLACING SYNTHETIC COLORANTS WITH COLORANTS EXTRACTED FROM BIXA ORELLANA SEEDS. - CHIRAG PANCHAL; EKTA SAPKAL; JIGAR PADHIAR; SWATI DESHMUKH (International Journal of Pharma and Bio Sciences, 2015)
Cosmetics are incredible in demand. Cosmetic includes various formulations.Among them, lip jelly is having very appreciable contribution in it. Lip jelly is having similar properties as compared to lipstick and lip balm which prevents the lips from environmental factors and colors them. Current market uses synthetic colorants in lip cosmetics which have various side effects. Nature is full of colors which are safer to human. So our team have targated different plants to extract natural colors from them and use for development of herbal lip jelly. Current formulation involves the development of lip jelly by using natural dye obtained from the seed coat of Bixa Orellana. It is evaluated for organolaptic properties like colour, odour, spread ability, pH, melting point, skin irritation etc. We can claim that developed formulation is having no side effects which can bechronically used by the women with great satisfaction.